The Efficacy of the Existing Laws in Regulating the Number of Street Children in Uganda - Esther Idia Nyikada (Uganda Christian University, 2024)
This research study is intended to analyze the legal framework governing street children in Uganda, the efficacy of those laws, whilst analyzing the possible reasons as to why children are being on streets as well as the risks faced by these particular children, much emphasis will be on the post-independence Era up to date focusing mostly in the Kampala Metropolitan Area. The research will also look at the possible solutions or ways of how to do away with the problem of children on streets while promoting and protecting their rights